Current treatment preferences in acute myeloid leukemia: a survey in Brazil - Portugal, Rodrigo Doyle (Hematol Transfus Cell Ther, 2020)
INTRODUCTION: : Most adults with acute myeloid leukemia (AML) will eventually relapse from their disease. The combination of 7-day cytarabine and an anthracycline on days 1–3 (the so called “7 + 3” regimen) can be considered standard of care of younger patients with AML. However, the treatment of the elderly ineligible for intensive chemotherapy remains a challenge. Low-dose of subcutaneous cytarabine or hypomethylating agents (HMA) have been studied this group. There are no studies investigating physician practice variation in treating AML in Brazil. METHODS: : We developed a survey with ten questions in order to explore the approach to AML in Brazil. RESULTS: : The sample size comprised 100 hematologists. Most reported regular (63%) or occasional (29%) treatment of AML patients. Karyotype analysis and polymerase chain reaction were available in 88% and 71% of institutions, respectively. Next generation sequencing analysis was used in 7% of instituitions. Younger patients receive the “7 + 3” protocol with continuous infusion of cytarabine and anthracycline in 98% of cases. The preferred anthracycline is daunorubicin (64%), followed by idarubicin (34%). The most prescribed daunorubicin dose was 60 mg/m(2) (56%). Consolidation after CR with high cytarabine doses (HIDAC) was indicated by 84% of hematologists and 70% use 3 g/m(2) twice a day for 3 days. Elderly and unfit patients received HMA (47%) as the preferred treatment. CONCLUSION: : We showed that the most prevalent AML treatments were according to current guidelines. There is room to improve on the availability of diagnostic tools and the capacity to perform bone marrow transplantation.